INFLUENCE OF MICROALLOYING BY BORON ON HARDENABILITY OF STEEL - E. P. Baradyntseva; N. A. Glazunova; O. V. Rogovtsova (Литьë и металлургия, 2016)
The research conducted in laboratory of metallurgical science by which the factors exerting impact on hardenability of steel microalloyed by boron were analysed. The research was made because the implementation of this process in mass production is connected with the certain difficulties. The conducted researches have allowed to draw a conclusion that changing content of various chemical elements, such as nitrogen, boron, the titan and aluminum in steel containing boron, produced by JSC «BSW – Management Company of Holding «BMC» at the stage of preparation of chart flowsheet make it possible to predict terms of hardenability of the final product.